Blunt liver trauma with concomitant injuries to the abdominal viscus: A dilemma for trauma surgeons - Dong Yi; Guo Yuyang; Jiang Yuxing; Liu Wenfei; Fang Yong (Srpski Arhiv za Celokupno Lekarstvo)
Introduction. Blunt liver trauma is predominantly managed non-surgically, yet the optimal treatment and timing for addressing its late complications remain uncertain. This study aims to evaluate treatment approaches and outcomes for blunt liver trauma with concomitant abdominal visceral injuries. Case Outline. We present two cases of adult males who sustained severe liver and other organ injuries due to road traffic accidents. Both patients underwent comprehensive treatment, including urgent laparotomy. The first case resulted in severe complications and eventual mortality, while the second case had a favorable outcome with conservative management of the liver hematoma. Conclusion. Retaining blood clots around the liver wound during surgical intervention may enhance hemostasis and reduce infection risks. Further controlled studies with larger samples are necessary to validate these findings.